2021
DOI: 10.3390/w13192795
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Earthquake-Induced Hydrologic Changes and Faults

Abstract: Hydraulic properties of fault zones are important to understanding the pore pressure development and fault stability. In this work, we examined the relationship between water level changes caused by the 2008 Wenchuan Mw 7.9 earthquake and faults using four wells with the same lithology around the Three Gorges Dam, China. Two of the wells penetrating the fault damage zones recorded sustained water level changes, while the other two wells that are not penetrating any fault damage zones recorded transient water l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The composition of groundwater affected by tectonic activity in fault zones or by earthquakes will be exceptional, and the injection of CO 2 is proposed as a main mechanism for the generation of the abnormalities [1][2][3][4][5][6].…”
Section: Relationship Between Water Chemistry Anomaly Of the Boiling-...mentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of groundwater affected by tectonic activity in fault zones or by earthquakes will be exceptional, and the injection of CO 2 is proposed as a main mechanism for the generation of the abnormalities [1][2][3][4][5][6].…”
Section: Relationship Between Water Chemistry Anomaly Of the Boiling-...mentioning
confidence: 99%
“…Seismic activities along faults or fractures may disturb the original equilibrium state of the water-rock interaction in the crust, resulting in abnormal changes in the chemical composition of gas and water in the groundwater [1][2][3][4][5][6]. Long-term observations have shown that the composition of groundwater near the Earth's surface and the gas composition in the soil sensitively record the stress and strain state of the Earth's crust [7,8].…”
Section: Introductionmentioning
confidence: 99%